ALT Trends Through Childhood and Adolescence and Association with Hepatic Steatosis at 24 Years. (29th May 2020) - Sekkarie, Ahlia; Figueroa, Janet; Northstone, Kate; Welsh, Jean; Vos, Miriam
Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome and is characterized by elevated levels of fat in the liver. NAFLD can begin in childhood, although the origins of the disease are not well characterized. Elevated alanine aminotransferase (ALT) is often used to screen for NAFLD. Our objectives are to 1) examine whether elevated ALT at 24 y is associated with hepatic steatosis and 2) describe whether ALT trends from 9 to 24 y differ by hepatic steatosis grade at 24 y. Methods: We used data from a UK population-based birth cohort study (ALSPAC). Patients with 2 to 4 ALT measurements (at 9, 15, 17, 24 y) were included; pregnant women and high alcohol consumers were excluded. To assess hepatic steatosis, controlled attenuation parameter (CAP) scores from Fibroscan were measured at 24 y. We categorized CAP scores into steatosis grades [none (S0: < 248 dB/m), mild/moderate (S1-S2: 248–279 dB/m), and severe (S3: >279 dB/m)]. We used a Pearson's chi-square test to determine whether elevated ALT at 24 y (>19 U/L in women, >30 U/L in men) was associated with steatosis grade. We used sex-stratified linear mixed models to assess trend differences of log-transformed ALT levels from 9 to 24 y between the different steatosis grades at 24 y. Results: The final sample size was 1156 (41.4% male). At 24 y, among those with elevated ALT, 17.5% had severe steatosis (S3), while among those with normal ALT only 4.8% had S3 ( P  < 0.001). In both sexes, there was a more rapid increase in ALT from 9 to 24 y in those with S3 vs S0 at 24 y ( P  < 0.001). In boys and girls at 9 y, there was no significant difference between ALT values for those with subsequent S3 v S0. In boys at 15 y, ALT was mean (95% CI) 19.1 U/L (17.4–20.9) for S3 vs 15.5 U/L (15.0–16.1) for S0; at 17 y, ALT was 25.4 U/L (23.3–27.8) for S3 vs 18.1 U/L (17.5–18.7) for S0; at 24 y, ALT was 45.2 U/L (40.6–50.4) at S3 vs 24.5(23.5–25.6) at S0 ( P  < 0.001 for all differences). In girls there were smaller but still significant differences in ALT values between those with S3 and S0 at 15, 17, and 24 y. Conclusions: Higher ALT levels from childhood to adolescence were associated with severe hepatic steatosis at 24 years. Diverging ALT trends prior to NAFLD diagnosis may allow for the identification and prevention of NAFLD. Funding Sources: The UK Medical Research Council and Wellcome and the University of Bristol Children's Healthcare of Atlanta.